ANALISIS TINDAK TUTUR DALAM CERAMAH KH ANWAR ZAHID - Fadilah, Nisaul (sarasvati, 2019)
A form of communication called speech, in which have the means and a particular purpose hanging from the context of tuturan delivered. A method to this research using methods documentation. This means that data in research is taken of the document is in youtube. The data were drawn from lectures given by KH Anwar Zahid who was a kiai is using his theory of Yule. The result of this research is (1) a speech act lokusi is to follow up said meaningful as expressed in speech or meaning they are. A lokusi consisted of three types namely inform, forbids the praises of, a speech act (2) ilokusi is also said that has meaning as acknowledged by Listener. (3) a speech act perlokusi is a speech act that is big with meaning the speakers of desired. A speech act perlokusi is composed of perlokusi perform the act of, perlokusi perlokusi a feeling of anger and a feeling of delightÂ